Implementation of public sector marketing in Indonesia: Internet-based study official provincial government website - Supriadi, Hary; Imbaruddin, Amir (Gema Wiralodra, 2023)
The quality of performance and public services in Indonesia still requires significant improvement. One approach that can be used to improve this quality is the application of marketing concepts. This research aims to identify the practice of implementing a marketing approach, especially the 4P1C strategy (product, price, place, promotion, and customer focus and relations) in the public sector in Indonesia. The method used is content analysis, where marketing strategy practices are detected through narratives on the official pages of provincial government agencies in Indonesia. 4,678 pages of text (1,126,018 words) were copied from 34 official Provincial Government websites for analysis. Analysis was carried out on manifest content using an a priori coding approach and hidden content supported by the QDA Miner application. The analysis results show that provincial governments in Indonesia still need to maximize the implementation of the 4P1C marketing strategy fully. The element of "promotion" became the dominant element of the process, with words such as "socialization" and "information" dominating usage. However, it is essential to note that the term "information" is more related to the obligation to disclose information by the law than persuasion efforts for promotional purposes. Apart from that, the provincial government does not use its official website as a marketing tool for its region (marketing place). Only a few provinces use narratives related to "investment," "regional potential," and "regional advantages" as marketing efforts. This research confirms the view of Lee & Kotler (2006) that marketing in the public sector is a field that still needs to be considered and understood by public sector managers. Thus, further efforts are required in order to increase understanding and application of marketing concepts in the context of public services in Indonesia.